2007
DOI: 10.3354/ame047011
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the concentration and metabolic activity of bacteria and viruses at an Antarctic coastal site

Abstract: Bacteria play a key role in the world's oceans, supporting nutrient remineralisation and mediating carbon transfer. Little is known about annual changes in bacterial concentration, production and metabolism during the extreme seasonal changes in biological productivity in Antarctic waters. We measured rates of bacterial production, concentrations of viruses and bacteria and environmental parameters between February 2004 and January 2005 at an Antarctic coastal site. Concentrations of total bacteria and viruses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
47
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 42 publications
12
47
1
1
Order By: Relevance
“…The low bacterial productivity and abundance of the initial community is characteristic of the post-winter bacterial community in Prydz Bay where growth is limited by organic nutrient availability (Pearce et al, 2007). Whilst an increase in cell abundance was observed at CO 2 levels ≥ 634 µatm (Fig.…”
Section: Ocean Acidification Effects On Bacterial Productivitymentioning
confidence: 93%
See 2 more Smart Citations
“…The low bacterial productivity and abundance of the initial community is characteristic of the post-winter bacterial community in Prydz Bay where growth is limited by organic nutrient availability (Pearce et al, 2007). Whilst an increase in cell abundance was observed at CO 2 levels ≥ 634 µatm (Fig.…”
Section: Ocean Acidification Effects On Bacterial Productivitymentioning
confidence: 93%
“…Samples for POM analysis, particulate organic carbon (POC), and particulate organic nitrogen (PON) were collected following the method of Pearce et al (2007). Equipment for sample preparation was soaked in Decon 90 (Decon Laboratories) for > 2 days and thoroughly rinsed in MilliQ water before use.…”
Section: Elemental Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, marine microbial observatories generally rely on coastal areas. Indeed, numerous studies have shown that bacterial abundance and activity vary at a seasonal scale G. Mével et al: Short-term variation in bacterial abundance and production in a large number of coastal waters (Shiah and Ducklow, 1994;Pinhassi and Hagström, 2000;Gerdts et al, 2004;Pearce et al, 2007;Sapp et al, 2007), but considerably less information is available in open Ocean (Ducklow and Carlson, 1992). Substrate availability and, to a lesser extent, temperature have been to be the main driving forces of bacterial abundance and production at a seasonal scale (Wikner and Hagström, 1999;Lemée et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Although a lower percentage of cells (~60%) were detected by Junge et al (2004) in sea ice sampled during the Arctic winter, this is likely to reflect seasonal variation in bacterial activity (e.g. Pearce et al 2007), and in general FISH detection rates appear to be significantly higher in sea ice than in other systems.…”
Section: Discussionmentioning
confidence: 86%